ANALISIS STRATEGI PENGEMBANGAN PRODUK BATIK SEMARANGAN DALAM MEMPERLUAS PASAR (Studi pada 5 (Lima) UKM Batik di Kota Semarang) - Rahayu Ningsih, Ardiyana Dwi; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
The developing batik industry is currently a handicraft that has high-value products, in the development of products carried out by UMKM Batik Semarang, which is able to produce new innovations and strategies in developing batik semarangan products. The results of research on the development and analysis of strategies carried out by UMKM Batik Semarang can increase consumer demand for batik products while seeing the demand for batik at this time. This study discusses the outline to find out how UMKM Batik Semarang conducts an analysis of product development strategies so that they can make semarangan batik products. This research is a qualitative research that uses descriptive analytic type with a focus of research on the strategies used in the process of developing batik semarangan products. The data retrieval method used is the interview method and document study, while the discussion room in this research completes all sections of UMKM Batik Semarang with key informants namely the owner and the company. The results show how the stages of product development have a relationship and influence one another. UMKM Batik Semarang emphasizes the development of product value by searching the market. The conclusion of this research is that in the product development process carried out by UMKM Batik Semarang produces a product development method called the Natural Color Concept and the embodiment of the work, in addition to that the brand story used in promoting products to the market, using social media. The challenge that addresses companies in this regard is how the company drives markets and maintains cultural heritage